(untitled) (Annals of Medical Research, 2021)
Aim: Scarce data are available for rectovaginal fistula (RVF) as a serious complication of low anterior resection with a double-stapled anastomosis for rectal cancer. In this study, we aimed to evaluate our surgical management of RVFs formed due to stapler use.Material and Methods: Between 2010 and 2018, patients who developed rectovaginal fistula after the use of circular stapler during rectal surgery were included. Clinic characteristics, type of surgical treatment performed and details of surgery in patients were retrospectively evaluated.Results: Ten patients for whom stapler device was used for rectal cancer surgery and diagnosed with RVF were included in our study. The mean age of the patients was 45.7±11.8 and mean BMI value was 27±2.4. For 9 patients who had primary repair for RVFs, 7 patients experienced recurrence after their first operation. For this subgroup, muscle flap was performed in 3, vaginal mucosa advancement flap 2, sartius flap one, and another primary repair plus fibrin glue application one patient. After the second interventions, two patients were managed with muscle flap creation and primary repair plus fibrin glue was required for one patient, for their recurrence. For patient who had primary repair plus fibrin glue application for her second operation, sigmoid colostomy followed by abdominoperineal resection was required for persisting complaints.Conclusion: The management of postoperative (RVF) after low anterior resection for rectal cancer is difficult and the results are often unsatisfactory. Endoanal mucosal flaps and muscle flaps are the treatment modalities we recommend, especially in patients with recurrence.Keywords: Circular stapler; rectovaginal fistula; rectal cancer.